Граничні можливості термоелектричних засобів вимірювання різниці температур з автоматичним налаштуванням - Яцук, В. О.; Здеб, В. Б.; Яцук, Ю. В. (Видавництво Львівської політехніки, 2018)
У багатьох галузях сучасної техніки використовуються вимірювачі різниці температур, від точності вимірювання якої залежать інші технологічні параметри контрольованих процесів, наприклад, у метеорології, вимірюванні витрат спожитої теплової енергії тощо. На основі термоелектричних перетворювачів можуть бути побудовані вимірювачі різниці температури для роботи в ширшому діапазоні температур порівняно з іншими типами сенсорів. Загалом точність вимірювання різниці температур визначається неідентичністю функцій перетворення сенсорів, значення якої забезпечується конструктивно-технологічними методами під час виготовлення. Її значення важко ідентифікувати в робочих умовах експлуатації та практично неможливо врахувати в структурах вторинних приладів для вимірювання різниці температур. У сучасній вимірювальній техніці кіберфізичні системи як розпорошені інтелектуальні системи на основі мереж фізичних та обчислювальних компонентів, які взаємодіють, забезпечують нові функціональні можливості щодо покращення якості процесів вимірювань. Запропоновано здійснювати автоматизоване оперативне налаштування метрологічних параметрів цифрових вимірювачів різниці температур під час експлуатації. Вторинний прилад запропоновано реалізовувати на основі програмованих на чипі структур з використанням кодокерованих багатозначних мір напруги. Показано, що під час розміщення обох термоелектричних перетворювачів у середовищах із відомими значеннями температури можна скоригувати похибки, спричинені інструментальними похибками сенсорів. Окрім того, за допомогою зміни кодів керування кодокерованими мірами напруги запропоновано визначати коефіцієнт перетворення вторинного приладу в певний момент часу та в заданих умовах експлуатації. Обговорено також можливості практичної реалізації цифрових вимірювачів різниці температур з автоматичним налагодженням у робочих умовах експлуатації.

The temperature differences meters are used in many branches of modern technology. Their accuracy is depending on other technological parameters of controlled processes, for example, in meteorology, measurement of the consumption of heat energy, etc. On the basis of thermoelectric converters, meters of temperature difference can be constructed for operation in a wider range of temperatures than other types of sensors. In general, the accuracy of difference temperature measuring is determined by the not identity of the sensors transformation functions. It value is provided by structural and technological methods in the manufacturing process. It is difficult to identify this spread value under operating conditions and it is virtually impossible to take into account in the secondary devices for measuring the temperature difference. In modern measuring technique, cyber-physical systems as scattered intelligent systems based on interacting networks of physical and computing components provide new functionalities for improving the quality of measurement processes. It is proposed to carry out automated operational setup of metrological parameters of digital meters of temperature difference during operation. The secondary device is offered to be implemented on the basis of chip-based programmable structures using codonvalued multi-valued voltage measures. It is shown that the outputs of both temperature sensors and outputs of the code controlled voltage measure can be connected to different inputs of the measuring device, with their switching and activation being carried out programmatically without additional hardware costs. The method of operative debugging of a digital temperature difference meter is proposed, which consists in the alternating placement of each of the thermoelectric transducers in media with known temperature values. At the same time, another source of differential input of the meter is connected to the output voltage of the code-controlled voltage measure, which is fed into a code proportional to the code of the known temperature values. It is proved that in this way it is possible to correct the errors caused by instrumental errors of the temperature sensors of both measuring channels. In addition, by changing the codes of control of the corded voltage measure, it is proposed to determine the conversion factor of the secondary device at the given time and in the given operating conditions. A detailed analysis of the errors was performed during the execution of the procedures for adjusting the parameters of both measuring channels. It shows how to identify corrective elements and how to use them in the process of counting the corrected result of measurement. It is noted that the nonlinear component of the uncorrected error value due to the nonlinearity of the sensors will determine the width of the range of measured temperature differences over the entire range of temperature sensor changes. Also discussed are the possibilities of practical implementation of digital temperature differential meters with automatic adjustment in working conditions of operation.
Limits of thermoelectric temperature difference measuring means with automatic adjustment
Keywords: вимірювач різниці температур; термоелектричний сенсор; кіберфізичні системи; коригування похибок; кодокеровані міри; автоматичне самоналаштування; temperature difference meter; thermoelectric sensor; cyber-physical systems; error adjustment; code-controlled measure; automatic settings